Adhesion of cells to surfaces coated with polylysine. Applications to electron microscopy (The Rockefeller University Press, 1975)
Cells of many kinds adhere firmly to glass or plastic surfaces which have been pretreated with polylysine. The attachment takes place as soon as the cells make contact with the surfaces, and the flattening of the cells against the surfaces is quite rapid. Cells which do not normally adhere to solid surfaces, such as sea urchin eggs, attach as well as cells which normally do so, such as amebas or mammalian cells in culture. The adhesion is interpreted simply as the interaction between the polyanionic cell surfaces and the polycationic layer of adsorbed polylysine. The attachment of cells to the polylysine-treated surfaces can be exploited for a variety of experimental manipulations. In the preparation of samples for scanning or transmission electron microscopy, the living material may first be attached to a polylysine- coated plate or grid, subjected to some experimental treatment (fertilization of an egg, for example), then transferred rapidly to fixative and further passed through processing for observation; each step involves only the transfer of the plate or grid from one container to the next. The cells are not detached. The adhesion of the cell may be so firm that the body of the cell may be sheared away, leaving attached a patch of cell surface, face up, for observation of its inner aspect. For example, one may observe secretory vesicles on the inner face of the surface (3) or may study the association of filaments with the inner surface (Fig. 1). Subcellular structures may attach to the polylysine-coated surfaces. So far, we have found this to be the case for nuclei isolated from sea urchin embryos and for the microtubules of flagella, which are well displayed after the membrane has been disrupted by Triton X-100 (Fig. 2).